Challenges in Grammar Learning Among EFL Students: A Case Study of an Indonesian University - Mustakim Mustakim; Nur Musfirah Jaya; Umiyati Jabri (Seltics Journal: Scope of English Language Teaching Literature and Linguistics, 2025)
This study investigates the grammar learning difficulties faced by first-semester English Education students at Muhammadiyah University of Enrekang. A qualitative research approach was employed, involving semi-structured interviews and document analysis of 14 students' academic records. The data were analyzed using thematic analysis, focusing on identifying recurring patterns in the students' experiences and challenges. The findings reveal three main categories of difficulties: cognitive challenges, instructional shortcomings, and environmental constraints. Cognitive challenges include struggles with understanding fundamental grammar concepts, such as tenses and subject-verb agreement, compounded by difficulties in retaining rules and applying them in practical contexts. Instructional shortcomings emphasize monotonous teaching methods, lack of contextualized practice, and insufficient feedback, which hinder students' progress. Environmental constraints, including limited exposure to English and inadequate social support, exacerbate these challenges. The study highlights the importance of adopting interactive, student-centered teaching methods and integrating grammar instruction into broader language skills. Practical recommendations include the use of innovative strategies such as project-based learning, grammar-focused digital tools, and the creation of English-speaking environments. These findings provide valuable insights for educators and policymakers to enhance the effectiveness of grammar instruction in EFL contexts and improve student outcomes.